EFEKTIVITAS MODEL PEMBELAJARAN LEARNING CYCLE 5E BERBANTUAN PERMAINAN TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI SUHU DAN KALOR DI SMP MUHAMMADIYAH 4 PEKANBARU - Vivia Melannia; Zulhelmi Zulhelmi; M. Nor M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Science learning in junior high schools still uses traditional learning which places the teacher as the center (teacher centered) dominated by the lecture method. Students active in the class, the learning cycle 5e learning model is used with the help of a talking stick game. The purpose of this study was to determine differences in student learning outcomes with classes that apply the learning cycle 5e learning model with conventional learning models. The type of research used is Quasy Experimental with Non-Equivalent Control Group Design. The samples in this study were students of SMP Muhammadiyah 4 Pekanbaru class VII.1 as the control class and class VII.2 as the experimental class consisting of 46 people. The data collection instrument was in the form of a learning achievement test which consisted of 10 multiple questions on temperature and heat. The data analysis used was descriptive analysis through cognitive learning outcomes and inferential analysis through normality, homogeneity, and independent T-test tests with the help of SPSS version 23. The results of this study were taken from descriptive analysis, namely the post-test score was found to be 76.08 with good category and inferential (sig) 0.008 <0.05 so that Ho is rejected, meaning that there are differences in cognitive learning outcomes of students between the experimental class and the control class. So it can be concluded that descriptive and inferential analysis can improve the cognitive learning outcomes of SMP Muhammadiyah 4 Pekanbaru students.Keywords :Model Learning Cycle 5e, Talking Stick Game, Cognitive Learning Outcomes, Temperature and Heat